Cardivascular Risk Profile in Patients with Diabetes and Acromegaly or Cushing’s Disease – Analysis from the DPV Database - Warncke, Katharina; Kummer, Sebastian; Kann, Peter Herbert; Bergis, Dominik; Bollow, Esther; Hummel, Michael; Zoicas, Flavius; Wernert, Sebastian; Holl, Reinhard W. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Although diabetes is a common complication of acromegaly or Cushing´s disease, there are only few detailed studies with a focus on cardiovascular risk, metabolic control or diabetes therapy. Here, we provide a comprehensive characterization from the longitudinal DPV (Diabetes Patienten Verlaufsdokumentation) registry.Methods Patients from the registry≥18 years of age with diabetes and acromegaly or Cushing´s disease were compared to patients with type 1 diabetes or type 2 diabetes using the statistical software SAS 9.4.Results Patients with diabetes and acromegaly (n=52) or Cushing’s disease (n=15) were significantly younger at diabetes onset (median age 50.1 and 45.0 vs. 59.0 years in type 2 diabetes; both p<0.05). Dyslipidemia was common in both diseases (71.0% and 88.9% vs. 71.8% in type 2 diabetes; n.s.), while hypertension was most frequent in acromegaly (56.8% vs. 20.9% in type 1 diabetes, p<0.00001). 36.5% of patients with acromegaly and 46.7% with Cushing´s disease receive insulin, compared to 50.4% with type 2 diabetes. Oral antidiabetic drugs were used in 36.5% of patients with acromegaly and 40% with Cushing´s disease, with a predominance of biguanides and dipeptidyl peptidase-4 inhibitors. HbA1c was well controlled in both groups (median 7.0% and 6.5%; vs. 7.2% in type 2 diabetes).Conclusion Patients with acromegaly are at a high risk for cardiovascular disease, reflected by dyslipidemia and hypertension. A high proportion of patients with diabetes in acromegaly or Cushing´s disease receives insulin. Based on a multicenter register, a sufficient number of patients with rare forms of diabetes can be analyzed.
Keywords: rare diabetes; insulin; oral antidiabetic drugs; metabolic control; diabetes registry